2019
DOI: 10.5799/jmid.657878
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Workers' Exposures for Mumps, Measles, Rubella and Varicella Zoster Virus Infections: A Multicenter Survey Study

Abstract: Objectives: In this research article, the authors carried out a multi-center study to evaluate the exposure and vaccination status of selected Turkish health-care workers for measles, rubella, mumps, and varicella zoster. Methods: The authors conducted a survey research by a questionnaire for health-care workers. The participants were questioned about vaccination and exposure of mumps, measles, rubella and varicella zoster virus. Results: A total of 5165 health-care workers; 1665 male (32.2%) and 3500 female (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In a multicenter study conducted with HCWs in our country, it was reported that only a small group (15.5%) was vaccinated for MMR. In our study, our pre-screening vaccination rate is similar to 12%; however, this rate increased to 34% after screening (26). Although the use of live viral vaccines such as MMR mimics the natural infection that provides life-long protection; Studies have shown that immunity is reduced even in fully vaccinated individuals, especially in measles and mumps (27).…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…In a multicenter study conducted with HCWs in our country, it was reported that only a small group (15.5%) was vaccinated for MMR. In our study, our pre-screening vaccination rate is similar to 12%; however, this rate increased to 34% after screening (26). Although the use of live viral vaccines such as MMR mimics the natural infection that provides life-long protection; Studies have shown that immunity is reduced even in fully vaccinated individuals, especially in measles and mumps (27).…”
Section: Resultssupporting
confidence: 50%
“…Some studies suggest that HCWs should be vaccinated without screening because it is not cost-effective (18). Despite this, it has been observed that staff vaccination rates are low in many centers (26). Since our vaccination rate was low, we decided to screen our staff with the decision of the Infection Committee Control, and we saw a significant increase in the rate of vaccination afterwards.…”
Section: Discussionmentioning
confidence: 91%